PENGEMBANGAN BUKU AJAR SISWA DAN BUKU GURU BERBASIS MATEMATIKA REALISTIK UNTUK MENINGKATKAN PENGETAHUAN, SIKAP DAN KETERAMPILAN MATEMATIKA SISWA KELAS VIISMPAL KARIM KOTA BENGKULU - Nurmita, Fina (Program Studi Pendidikan Matematika FKIP Unlam Banjarmasin, 2017)
The research aims to produce a studentâs text book and a teachersâ guide book with realistic mathematic as the fundamentals. The objectives are to increase knowledge, attitude, and mathematical aptitude of studentsâ of SMP Al Karim Bengkulu. The Research was an experimental research seeking to produce studentsâ text book and teachersâ guide book in order to help reader better comprehends the concept of two-dimensional figure, rectangle, and triangle. In order to develop the design, there were four steps of the research: defining, designing, developing, and disseminating. The research object was VII class students if SMP Alkarim Bengkulu academic year of 2014/2015 that comprised of 17 students, consisted of 8 male and 9 female. The current findings have several conclusions regarding the ideal criteria of better studentsâ text book and teachersâ guide book with realistic mathematic as the fundamental: 1) It should be able to help students constructing the knowledge instead of merely receiving the knowledge; 2) in order to be able to improve studentâs attitude, the book should be designed to provoke curiosity and students class participations; 3) in order to be able to increase mathematical aptitude, it should be able to increase studentsâ mathematical skill as well as observation skill,Â and using the formulation that has previously given. The Research findings have indicated that the book with aforementioned criteria was able to help the students reaching better score with average of 80.02 and 76 percent of students in the class were able to reach higher score above the pre-determined standard (KKM). Findings from the observation sheets have also shown that students were able to reach 4.1 score or in other words the students were highly active and involve during the study process. Findings from the mathematical aptitude sheets have concluded that the students were able to reach 4.03 score or in other words were highly creative.Â Keywords: Developing Studentsâ Text Book and Teachersâ Guide, realistic mathematic, mathematical knowledge, attitude, mathematical aptitude.